Indigenous plants used by the Otuo tribe of Owan East Local Government Area, Edo State, Nigeria - MacDonald Idu; Ovuakporie-Uvo Oghale; Ima-Osagie O. Sarah (Journal of Medicinal Plants for Economic Development, 2017)
Background: Traditional medicine remains an integral part of the Otuo tribe in Owan East Local Government Area of Edo State.